Asthma with recurrent middle lobe syndrome in children: Clinical features and lung function patterns - Feng, Yong; Yu, Haoting; Liu, Xin; Chen, Ning; Shang, Yunxiao; Zhang, Han (Frontiers in Pediatrics, 2023)
Background: Middle lobe syndrome (MLS) is a complication of childhood asthma. This study aimed to compare the clinical features and lung function between asthmatic children with recurrent MLS and transient right middle lobe (RML) and/or lingula atelectasis. Methods: This study retrospectively analyzed asthmatic children with RML and/or lingula atelectasis between 2010 and 2020 using data from the pediatric pulmonary department. According to the episodes of atelectasis, children were divided into recurrent (≥ 2 episodes) and non-recurrent (only 1 episode) MLS groups, to compare clinical features and lung function. Spirometry during acute asthma exacerbation and stable stages were recorded, and variations were calculated. Results: A total of 35 children with asthma and RML and/or lingula atelectasis were included, 15 of whom had recurrent MLS. The recurrent MLS group had a higher proportion of girls, infections, family allergy history, severe asthma, severe exacerbation, and higher levels of total IgE than the non-recurrent MLS group (P < 0.05). The recurrent MLS group had a significantly higher % predicted and z-scores for forced expiratory volume in 1 s (FEV1) and forced vital capacity (FVC), a greater proportion of high FEV1 and higher variations in FEV1 and FVC than that in the non-recurrent group (P < 0.05). After excluding children with mild to moderate asthma in the recurrent MLS group, the differences in clinical features disappeared, but the results regarding lung function remained similar, when compared to severe asthma patients without RML and/or lingula atelectasis. Conclusions: Childhood asthma with recurrent MLS has more frequent severe asthma and exacerbation but high lung function and variations.